Higher-order Nonclassicality in Superposition of Three-mode Photon-added Trio Coherent State - Tran, Quang Dat; Ho, Sy Chuong; Dao, Van Hung; Duc, Truong Minh (Communications in Physics, 2022)
In this paper, we study some higher-order nonclassical properties of the superposition of three-mode photon-added trio coherent state such as antibunching, squeezing, and entanglement. The results show that in the case with fixed the higher-order, when increasing the numbers of added photons, the manifestation of the higher-order three-mode sum squeezing is more obvious, but the degrees of higher-order antibunching, and higher-order three-mode entanglement are more reduced. Besides, with fixed the numbers of photon addition to the superposition of three-mode photon-added trio coherent state, the higher-order nonclassical properties as antibunching and entanglement are more pronounced, but three-mode sum squeezing is more decreased when increasing the number of the higher-order.